The Effect of Moringa (Moringa Oleifera L.) Leaf Extract Capsules in Increasing Hemoglobin Levels in Adolescent Girls - Novie Mauliku; Flora Honey Darmawan; Hana Yuliana; Farida Murtiani; Norma Norma (Indonesian Journal of Global Health Research, 2025)
Moringa leaves can be an alternative to increase hemoglobin (hb) levels because they contain high iron, protein, and vitamin C. Adolescent girls have a higher risk of experiencing anemia due to increased iron requirements resulting from menstruation. Objective: To determine the effect of moringa leaf extract capsules (Moringa Oleifera L) on increasing hemoglobin levels in teenage girls at SMKN 1 Takokak, Cianjur Regency. Method: The research design employed in this study is a pre-experimental approach, utilizing a one-group pretest-posttest design. The sample size consists of 30 adolescent girls selected through purposive sampling technique. Data collection involves measuring hemoglobin levels. Data analysis is conducted through univariate and bivariate analyses using the Wilcoxon Signed Rank Test. Results: The research findings indicate that there was an increase in hemoglobin levels before (10.69) and after (12.78) the intervention, with an average difference of -2.09. Furthermore, there was a significant p-value of 0.001 (<0.05). Conclusions: The moringa leaf extract capsules have shown an influence in increasing the hemoglobin levels of adolescent girls. Moringa Leaf Extract can be recommended as a non-pharmacological alternative to enhance hemoglobin levels.